Flexibility and resilience of great tit (Parus major) gut microbiomes to changing diets - Bodawatta, Kasun H; Freiberga, Inga; Puzejova, Katerina; Sam, Katerina; Poulsen, Michael; Jønsson, Knud A (Animal microbiome, 2021)
BACKGROUND: Gut microbial communities play important roles in nutrient management and can change in response to host diets. The extent of this flexibility and the concomitant resilience is largely unknown in wild animals. To untangle the dynamics of avian-gut microbiome symbiosis associated with diet changes, we exposed Parus major (Great tits) fed with a standard diet (seeds and mealworms) to either a mixed (seeds, mealworms and fruits), a seed, or a mealworm diet for 4 weeks, and examined the flexibility of gut microbiomes to these compositionally different diets. To assess microbiome resilience (recovery potential), all individuals were subsequently reversed to a standard diet for another 4 weeks. Cloacal microbiomes were collected weekly and characterised through sequencing the v4 region of the 16S rRNA gene using Illumina MiSeq. RESULTS: Initial microbiomes changed significantly with the diet manipulation, but the communities did not differ significantly between the three diet groups (mixed, seed and mealworm), despite multiple diet-specific changes in certain bacterial genera. Reverting birds to the standard diet led only to a partial recovery in gut community compositions. The majority of the bacterial taxa that increased significantly during diet manipulation decreased in relative abundance after reversion to the standard diet; however, bacterial taxa that decreased during the manipulation rarely increased after diet reversal CONCLUSIONS: The gut microbial response and partial resilience to dietary changes support that gut bacterial communities of P. major play a role in accommodating dietary changes experienced by wild avian hosts. This may be a contributing factor to the relaxed association between microbiome composition and the bird phylogeny. Our findings further imply that interpretations of wild bird gut microbiome analyses from single-time point sampling, especially for omnivorous species or species with seasonally changing diets, should be done with caution. The partial community recovery implies that ecologically relevant diet changes (e.g., seasonality and migration) open up gut niches that may be filled by previously abundant microbes or replaced by different symbiont lineages, which has important implications for the integrity and specificity of long-term avian-symbiont associations.
Keywords: 16S rRNA gene; Bacterial communities; Illumina MiSeq; Community flexibility; Community resilience; Gut symbionts